Analisis Faktor-Faktor Yang Mempengaruhi Kepuasan Nasabah Menggunakan Layanan Non Tunai Berbasis Teknologi Di Bank Syari’ah Mandiri Cabang Jambi - Machfia Win Hidayat (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2020)
The issues raised were: Does the quality of service, low cost, and speed of transactions affect customer satisfaction using technology-based non-cash services at Bank Syariah Mandiri Jambi branch? How is customer satisfaction using technology-based non-cash services at Bank Syariah Mandiri Jambi branch? The objectives of this research are: To find out whether low cost, transaction speed, and service quality have a significant effect on customer satisfaction using technology-based non-cash services at BSM Jambi Branch. To find out how customer satisfaction is using technology-based non-cash services at Bank Syariah Mandiri Jambi Branch. The research method used is a descriptive quantitative approach. It was explained that of the three variables only service quality (x1) and low cost (X2) had a significant effect on customer satisfaction at Bank Mandiri Syariah Jambi Branch. Meanwhile, transaction speed (X3) has no significant effect on customer satisfaction using non-cash services at Bank Mandiri Syariah Jambi Branch.